PENINGKATAN KEMAMPUAN BERHITUNG MENGGUNAKAN METODE JARIMATIKA PADA PESERTA DIDIK KELAS IV SDK 051 WAIGETE - Yustina Yani; Magdalena Dhema Dhema; Agnesia B. Anomeisa (IKIP Siliwangi, 2022)
This study aims to improve the ability to calculate multiplication operations using the Jarimatika method for fourth-grade students at SDK 051 Waigete. The variable that is the target of change in the research is the increase in numeracy skills using the Jarimatika method in the multiplication operation material, the action research used is the Jarimatika method. The research method is classroom action research which is carried out in two cycles, namely, cycle I and cycle II. The subject of the study was directed to all fourth-grade students with a total of 23 students. Data collection techniques were tests and observations. The data analysis technique used was the descriptive data analysis technique.From the results of the study, it can be concluded that the ability to count using the Jarimatika method in the multiplication operation material for fourth-grade students at SDK 051 Waigete is in the highly improved category. In the initial conditions before taking the action, the average value of students who passed was 61.30 and the percentage who passed was 30.43%, the first cycle the average value of students who passed was 61.86 and the pass percentage was 47.82%. and the second cycle average value obtained by students who passed was 92.13 and the percentage value that passed was 91.30%. Therefore, it is concluded that the use of the Jarimatika method can improve the arithmetic ability of multiplication operations in fourth-grade students at SDK 051 Waigete.